Complexity of an Homotopy Method at the Neighbourhood of a Zero - Yakoubsohn, J. C.; Gutierrez, J. M.; Magreñán, Á. Alberto (Advances in iterative methods for nonlinear equations, 2020)
This paper deals with the enlargement of the region of convergence of Newton's method for solving nonlinear equations defined in Banach spaces. We have used an homotopy method to obtain approximate zeros of the considered function. The novelty in our approach is the establishment of new convergence results based on a Lipschitz condition with a L-average for the involved operator. In particular, semilocal convergence results (Kantorovich-type results), as well as local convergence results (gamma-theory) are obtained.
Keywords: convergence; equations; newtons; Scopus(2); WOS(2)